2022
DOI: 10.1186/s12913-022-08051-w
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive survey of substance use treatment facilities in Uasin Gishu County Kenya

Abstract: Background Substance use disorders are a major problem in Uasin Gishu County, Kenya. The objective of this study was to describe the existing resources within substance use treatment facilities in the County, with the aim of guiding policy and interventions. Methods This was a cross-sectional study. We collected data from six substance use treatment facilities within Uasin Gishu County between August and November 2021. We used a researcher-designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Two other barriers to care that emerged in the literature were gender, with women consistently accessing SUD treatment at lower rates [ 22 – 24 , 26 , 34 , 36 39 ] and linguistic and ethnic discordance between treatment-seekers and providers [ 38 , 39 ]. A general lack of availability of services was attributed to multiple factors, including a paucity of investment on the part of regional and national governments [ 40 , 42 , 43 , 45 ]. This review also found that across countries psychiatric facilities are treating a large volume of patients with SUD, or those with SUD and a cooccurring psychiatric illness [ 18 , 19 , 21 , 23 – 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two other barriers to care that emerged in the literature were gender, with women consistently accessing SUD treatment at lower rates [ 22 – 24 , 26 , 34 , 36 39 ] and linguistic and ethnic discordance between treatment-seekers and providers [ 38 , 39 ]. A general lack of availability of services was attributed to multiple factors, including a paucity of investment on the part of regional and national governments [ 40 , 42 , 43 , 45 ]. This review also found that across countries psychiatric facilities are treating a large volume of patients with SUD, or those with SUD and a cooccurring psychiatric illness [ 18 , 19 , 21 , 23 – 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A heavy reliance on out-of-pocket payments was also observed in a psychiatric hospital treating patients with SUD, where more than 70% of patients paid out of pocket [ 23 ]. The cost barrier to treatment was echoed by a study of people who use heroin in three Kenyan cities, who reported a strong desire to receive residential treatment but inability due to an average cost of 114 USD per month [ 42 ]. Financial barriers were also shown to hinder treatment access in South Africa [ 41 , 43 ].…”
Section: Treatment Demand and Accessmentioning
confidence: 99%
See 2 more Smart Citations